Anna Paterson Stout : portrait of a New Zealand lady, 1858-1931 : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University - Webb, Monica R. (Massey University, 2015)
Lady Anna Paterson Stout was one of the most widely-known advocates for women in New Zealand in her lifetime (1858-1931) and a leading figure of the early women’s movement. During the course of her life, which corresponded to New Zealand’s development from settler society to established Dominion, and due to her marriage to Sir Robert Stout, she knew personally, worked with or influenced nearly every leading political, social and activist figure of that period. Why surprisingly little is known about her today forms one of the central questions to this thesis. This thesis analyses Anna’s life in light of historians Mary Beard and Gerda Lerner’s advocacy of women as force in their generations. It also explores Anna’s deliberate use of influence within the unique context of early female political equality as well as her willingness to act deliberately and independently from her more famous husband as a conscious exemplar of the New Woman. This thesis broadens our understanding of the personal relationships between the early leading women of New Zealand, such as Kate Sheppard, with whom Anna worked closely and often controversially. It also looks closely at Anna’s transnational engagement with the British suffrage movement in London during the critical years of 1909 to 1914. A study of the life of Anna Stout opens up numerous further avenues of inquiry as well as contributing to our understanding of New Zealand’s development in the immediate post-suffrage era. The thesis concludes that Anna Stout was a radical for her time and one who consciously used her access to centres of influence to publicly advance the cause of women on multiple levels.
Keywords: Anna Paterson Stout; Women's movements, New Zealand; Women's suffrage; Suffrage movement; Women's rights, New Zealand